Manejo del suelo en la Altillanura de los Llanos Orientales de Colombia - Gómez, Jaime (International Center for Tropical Agriculture, 2010)
Soil management in the Altillanura of Colombia’s Eastern Plains The strategies used for adequate soil management for the Altillanura (high plains with flat topography) of Colombia’s Eastern Plains are reviewed to establish modern, efficient, and sustainable livestock systems in this region. Advances in technology development within the technical and scientific cooperation agreement signed between Colombia’s Ministry of Agriculture and Rural Development (MADR) and CIAT, as well as those of the Center’s Soils Project and several national institutions co-partners in the agreement. Among the various strategies developed and applied in the region, the advances made in soil improvement are highlighted, in particular the recovery of degraded soils by building an arable layer. Other aspects related to soil improvement and management are also addressed, such as the adequate use of machinery and agricultural implements, agropastoral systems (especially the rice-pasture system), direct planting systems, and conservation and precision agriculture.